INTEGRATION OF REHABILITATION THERAPY AND PSYCHOLOGICAL SUPPORT TO REDUCE RELAPSE AND IMPROVE RETURN QUALITY TO SPORTS ACTIVITY AFTER INJURY - Hegel, Saif Salah Hassan; Hamidi, Ali Khayoon Tarish (Universitas Negeri Jakarta, 2026)
Background. Significant advancements in sports injury treatment and rehabilitation programs, relapse rates after returning to athletic activity remain a real challenge for both athletes and specialists. Field experience indicates that many athletes return to activity after regaining apparent physical fitness, but lack full psychological readiness, increasing their likelihood of recurring injuries. Objectives. The study aims to identifying impact of integrating rehabilitation therapy and psychological support in reducing relapse rates among athletes after injury. Method. The researcher adopted experimental method using a quasi-experimental design Two-Group Pretest-Posttest Design, as it was suitable for nature of study, which aimed to investigate effect of integrating rehabilitation therapy and psychological support in reducing relapse and improving quality of return to athletic activity after injury. Sample was divided into two groups experimental group is subject to an integrated rehabilitation program physical and psychological support. Control group undergoes a traditional physical rehabilitation program without organized psychological intervention. Pre- and post-tests were performed for both groups, in addition to a follow -up test to monitor relapse rates after returning to activity. Results. Results showed integration of rehabilitation therapy and psychological support has proven to be clearly effective in reducing relapse rates compared to traditional physical rehabilitation. Integrated rehabilitation program contributed to improving quality of return to sports activity to a statistically significant degree. Integrating psychological support into the rehabilitation program significantly reduced level of fear of recurrence. Conclusion. Physical-psychological integration has contributed to enhancing level of motor confidence among injured athletes. Results confirm importance of adopting a comprehensive, integrated approach in sports rehabilitation programs that balances physical and psychological readiness.